Extra-Hepatic Islet Transplantation: Validation of the h-Omental Matrix Islet filliNG (hOMING) Technique on a Rodent Model Using an Alginate Carrier. Issue 8 (August 2018) - Schaschkow, Anaïs; Sigrist, Séverine; Mura, Carole; Dissaux, Caroline; Bouzakri, Karim; Lejay, Anne; Bruant-Rodier, Catherine; Pinget, Michel; Maillard, Elisa
Following the tremendous development of hydrogels for cell therapy, there is now a growing need for surgical techniques to validate in vivo scaffold benefits for islet transplantation. Therefore, we propose a newly designed surgical procedure involving the injection of hydrogel-embedded pancreatic islets in the omentum, which is considered a favorable environment for cell survival and function. Our technique, called h-Omental Matrix Islet filliNG (hOMING) was designed to test the benefits of hydrogel on islet survival and function in vivo . Islets were implanted in the omentum of diabetic rats using the hOMING technique and alginate as an islet carrier. Blood glucose and C-peptide levels were recorded to assess graft function. After 2 months, grafts were explanted and studied using insulin and vessel staining. All rats that underwent hOMING exhibited graft function characterized by a glycemia decrease and a C-peptidemia increase ( P < 0.001 compared with preoperative levels). Furthermore, hOMING appeared to preserve islet morphology and insulin content and allowed the proper revascularization of grafted islets. The results suggest that hOMING is a viable and promising approach to test in vivo the benefits of hydrogel administration for islet transplantation into the omental tissue.